Determination of the Total Phenolic Contents, Antimicrobial and Antioxidant Effects in the Ethanolic Leaf Extract of Prunus Amgydalus - Edewor-Kuponiyi Theresa Ibibia (Journal of Applied Pharmaceutical Science, 2013)
The results showed that the maximum yield of flavonoids (26.54 mg/ml quercetin equivalent) can be obtained with 80% ethanol (v/v), extraction temperature of 80oC and raw material to solvent ratio of 0.048 g/ml. The results revealed presence of flavonoids, saponins, alkaloids and glycosides. The leaf extract was active against Pseudomonas aeruginosa, and Staphylococcus aureus with MIC of 0.05 mg/ml while it was inactive against Pseudomonas selanacea, Fusarium oxysporum, Kliebsella pnuemoniae, Escherichia coli, Bacillus subtilis, Bacillus cereus and Candida albacans. The total phenolic and flavonoid contents obtained were 40.35 mg/ml Gallic acid equivalent and 26. 54 mg/ml quercetin equivalent while the antioxidant assay showed a concentration dependent antiradical activity resulting from reduction of DPPH, SO and OH radicals to non radical forms. The scavenging activity of the ascorbic acid was seen to be higher than that of the extract.
Keywords: Prunus amygdalus, antimicrobial